اقوالِ فردوسی و حکمتِ قرآنی: حماسہ و اخلاق کا تقابلی استدلالی مطالعہ: Ferdowsi’s Sayings and Qur’anic Wisdom: A Comparative and Analytical Study of Epic Spirit and Ethical Paradigms (Qualitative Research Journal for Social Studies, 2025)
This study explores the intellectual and spiritual nexus between Ferdowsi’s epic expressions and the Qur’anic wisdom, focusing on the intertwined themes of valor, morality, and universal guidance. Ferdowsi, rooted in the socio-cultural milieu of medieval Persia, employed heroic narratives to instill courage, loyalty, and national identity, while the Qur’an established a holistic framework where bravery is coupled with self-restraint, justice, and moral equilibrium. Through a comparative lens, the research highlights convergences in ethical ideals—such as justice, fidelity, generosity, and honesty—while also delineating divergences, particularly between Ferdowsi’s ethnocentric orientation and the Qur’an’s universal and timeless message. In an era of global crises and moral disorientation, the study argues that Ferdowsi’s epic ethos, when juxtaposed with the Qur’anic ethical vision, provides both inspiration and practical guidance for constructing a society grounded in justice, resilience, and peace. This analytical synthesis underscores the enduring relevance of literary heritage and divine revelation in addressing contemporary human challenges.